The Relationship between Talent Acquisition Strategies and Employee Engagement - Yahcob, Mohamad Shafie; Rodzalan, Shazaitul Azreen (Research in Management of Technology and Business, 2025)
This study explores the relationship between talent acquisition strategies and employee engagement. In today's competitive business landscape, organizations must strike a balance between talent acquisition strategies and employee engagement to succeed. Attracting qualified candidates, effective talent recruitment practices lay the groundwork for significant employee engagement, which is crucial for achieving organizational goals. A company's ability to attract and retain top talent is dependent on its talent acquisition strategy. When the right talent was detected and suited to the company culture. Thus, employees are more likely easier to be engaged. The relationship between talent acquisition strategies and employee engagement is a key driver of organizational success. Talent acquisition involves not only attracting qualified candidates but also ensuring that these individuals align with the organization’s culture and long-term goals. This alignment leads to higher levels of engagement, which in turn benefits the organization through increased productivity, better job satisfaction, and improved retention. Therefore, businesses must view talent acquisition and employee engagement as interconnected and strategic processes that, when executed effectively, can propel the organization to achieve its goals and maintain a competitive edge in the market.